Generalizations of the Josephus problem - Thériault, Nicolas (Utilitas Mathematica, 2000)
This article presents two algorithmic solutions to an extended version of the Josephus problem. In addition, the number of steps required for one of these algorithms is discussed. Finally, a variation on the Josephus problem and an algorithmic solution to this new problem are also given.